Multi-Sectoral Analysis of Strategic Groups in Franchising: A Study in Italy // Análisis multisectorial de grupos estratégicos en franquicias: un estudio en Italia - Ramírez-Hurtado, José M.; Quattrociocchi, Bernardino (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2018)
Franchising is a commercial form which enables firms to successfully penetrate the market and expand in an environment of growing global competitiveness. This form of business is present in many different activities and sectors, having its own characteristics and structures and significant differences among firms. It is therefore important to identify possible homogeneous groups of franchisors which share the same business strategies. This work is centred on the system of franchises in Italy. The figures about the high number of franchisors and franchised establishments, the quantity of chains operating over many years and the high penetration in the different sectors mean that franchising in Italy has a high degree of competitiveness and maturity. All this, along with the scarcity of studies about strategic groups in franchising in Italy, justifies this study. Specifically, the objectives are: 1) to identify the possible existence of strategic groups in Italy’s franchising system; 2) to carry out a multisectoral analysis of strategic groups to determine whether the same strategic groups exist in the different franchising sectors; and 3) to characterise the different strategic groups and show their most significant variables. The results indicate that the most numerous strategic group is made up of chains which fully trust the domestic market, so the majority have not undertaken a strategy of internationalisation. On the other hand, the least numerous strategic group is composed of chains which have grown rapidly. This reaffirms the degree of saturation of the franchising market in Italy, as there is a great number of brands but few franchised establishments. The results attained in this work allow an understanding of the keys to the success of franchises in the Italian market for the franchisors to be able to maintain their position or, contrariwise, make changes and reposition themselves. ———————————– La franquicia es una forma comercial que permite a las empresas penetrar con éxito en el mercado y expandirse en un entorno de creciente competitividad global. Esta forma de negocio está presente en muchas actividades y sectores diferentes, con sus propias características y estructuras y diferencias significativas entre las empresas. Por lo tanto, es importante identificar posibles grupos homogéneos de franquiciadores que compartan las mismas estrategias comerciales. Este trabajo se centra en el sistema de franquicias en Italia. Las cifras sobre el alto número de franquiciadores y establecimientos franquiciados, la cantidad de cadenas que operan a lo largo de muchos años y la alta penetración en los diferentes sectores hacen que las franquicias en Italia tengan un alto grado de competitividad y madurez. Todo esto, junto con la escasez de estudios sobre grupos estratégicos en franquicias en Italia, justifica este estudio. Específicamente, los objetivos son: 1) identificar la posible existencia de grupos estratégicos en el sistema de franquicias de Italia; 2) llevar a cabo un análisis multisectorial de grupos estratégicos para determinar si existen los mismos grupos estratégicos en los diferentes sectores de franquicias; y 3) caracterizar los diferentes grupos estratégicos y mostrar sus variables más significativas. Los resultados indican que el grupo estratégico más numeroso está compuesto por cadenas que confían plenamente en el mercado interno, por lo que la mayoría no ha emprendido una estrategia de internacionalización. Por otro lado, el grupo estratégico menos numeroso está compuesto por cadenas que han crecido rápidamente. Esto reafirma el grado de saturación del mercado de franquicias en Italia, ya que hay un gran número de marcas pero pocos establecimientos franquiciados. Los resultados obtenidos en este trabajo permiten comprender las claves del éxito de las franquicias en el mercado italiano para que los franquiciadores puedan mantener su posición o, por el contrario, realizar cambios y reposicionarse.